Avaliação prostpectiva de heparam sulfato, condroitim sulfato e ácido hialurônico em pacientes com câncer de próstata - Silva, Matheus Neves Ribeiro Da [UNIFESP] (2018)
Prostate cancer in Brazil represents the most common type of cancer among men after skin cancer. Although there are effective tests for the diagnosis of prostate cancer, there are still discussions about the most appropriate and non-invasive method for such diagnosis, always looking for less invasive methods to evaluate the possible prognosis of the disease. The present study aimed to evaluate urinary levels of chondroitin sulfate (CS) and heparan sulfate (HS), as well as plasma levels of hyaluronic acid (HA) in patients with prostate cancer, before and after treatment, compared with individuals which was not affected by neoplasia. Plasma samples were used to quantify AH and urine for CS and HS quantification from forty-four patients with prostate cancer and fourteen controls (non-affected individuals). Laboratory and pathological clinical data were correlated with the quantification of glycosaminoglycans by statistical analysis. There was no difference in the urinary levels of CS and HS among patients with prostate cancer and the control group. However, sulfated glycosaminoglycans (HS and CS) were analyzed in urine samples collected before and after treatment, and an increased in urinary excretion of heparan sulfate was observed after surgery, followed by decrease in the excretion of chondroitin sulfate after hormone therapy. The level of serum hyaluronic acid showed a significant increase in patients with prostate cancer (39.68 ± 30.00 ng / ml), compared to the control group (15.04 ± 7.11 ng / ml), p = 0.004. We also observed a significant increase in hyaluronic acid in patients with high-risk of prostate cancer, following the D'Amico classification, compared to low-risk patients (p = 0.0214). Patients submitted to surgery had a significant reduction in the level of AH (p = 0.029). The quantification of serum hyaluronic acid represents a noninvasive test with potential use in the diagnostic and prognostic evaluation of prostate cancer. Future studies are essential to confirm the unprecedented but preliminary results obtained in the present study.